Tripartite motif 27 promotes cardiac hypertrophy via PTEN/Akt/mTOR signal pathways. Issue 4 (1st April 2022) - Chen, Yan; Liu, Zewen; Hu, Zhengqing; Feng, Xiuyuan; Zuo, Li
ABSTRACT: Tripartite motif-containing 27 (Trim27) is highly expressed in tumor cells and regulates natural immunity and apoptosis. However, the effects of Trim27 in cardiac hypertrophy are not fully elucidated. In this study, we explored the potential role of Trim27 in pressure overload-induced cardiac hypertrophy and the underlying mechanism. The results indicated that compared to sham operation (Sham) group, transverse aortic constriction (TAC) group showed significantly up-regulated Trim27 protein expression (P < 0.05). The neonatal rat cardiomyocytes (NRCMs) were isolated and stimulated with PBS, angiotensin (AngII) and phenylephrine (PE). NRCMs were collected to detect the protein expression of Trim27. The results were consistent with the results in vivo. Compared to PBS treatment, the expression of Trim27 protein in NRCMs was significantly increased after PE or AngII stimulation (P < 0.05, respectively). Knockout of Trim27 reduced the size of cardiomyocytes and the protein expression of ANP, BNP, and β-MHC, improved cardiac function, and decreased myocardial hypertrophy (P < 0.05). Trim27 may be involved in regulating the development of cardiac hypertrophy. Further results showed that Trim27 enhanced the protein expression of phosphorylation of Akt, GSK3β, mTOR, and P70s6k by interacting with PTEN (phosphatase tensin homolog). These findings revealed that Trim27 can promote cardiac hypertrophy by activating PTEN/Akt/GSK3β/mTOR signaling pathways.